Réponses

2013-11-05T14:47:43+01:00
Bonjour
on sait que 
f est définie sur [ -5; 3 ] 
f croissante sur  [ -5 ; -1 ]  puis décroissante sur [ -1 ; 3 ] 
f(-1) = 4 
f(-5)= -1 
A ( 3; -3/2)  donc f(3) = -3/2
f(0) = 3/2
f(x) =0   pour x= -3  et x = 1 
tableau

x          -5                  -3                -1              1                 3
f(x)        -1                 0                 4               0                 -3/2
f(x)        -1         croissante            4          décroissante      -3/2